DEGRADATION PROCESSES AND THEIR MANIFESTATION IN THE STRUCTURE OF THE SOIL COVER OF PASMOVE POBUZHZHIA - Haskevych , О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Soil degradation processes, exacerbated by agrogenic activities, have a profound impact on both the properties of individual soil types and the overall diversity and heterogeneity of the soil cover. These processes disrupt the natural balance of the soil ecosystem, leading to significant changes in soil composition and structure. A comprehensive study was conducted in the key area "Nadychi" (Lviv district, Lviv region) to assess the influence of degradation processes on the soil cover structure of Pasmove Pobuzhzhia. The soil cover in this region comprises a variety of soils, including automorphic (gray forest, dark gray podzolized), semi-hydromorphic (meadow, sod), and hydromorphic (peatlands) types. These soils form complex combinations, variations, mosaics, and tashets, each contributing to the region's intricate soil landscape. The study meticulously analyzed the geometric structure, classification diversity, contrast, and heterogeneity of the identified soil combinations. Erosion processes were a significant focus, particularly their impact within variations, combinations, and mosaics of the soil cover. A substantial proportion of these areas showed severe signs of soil erosion, with erosion rates reaching 50% and, in some cases, even 80%. Plane washout and linear erosion were particularly prevalent, leading to the degradation of soil quality and further complicating the soil structure. Soil combinations containing eroded soils displayed higher levels of fragmentation and complexity, characterized by an increased number of soil habitats and the emergence of more complex shapes. These shapes often took the form of elongated and tree-like micro-catenas, contributing to the overall heterogeneity of the soil cover. The contrast in the soil cover was largely driven by genetic differences, particle size distribution, and the degree of soil erosion, with erosion being the predominant factor. The contrast coefficient, attributed to soil erosion, varied significantly across the key area, ranging from 7.37 to 66.1% in different soil combinations. Moreover, the integral index of soil cover heterogeneity was highest in combinations, ranging from 11.59 to 49.15, indicating the maximum complexity and contrast observed in the soil cover.